Sustainability Reporting and Good Corporate Governance: The Key to Financial Performance in Indonesia’s Mining Sector 2021–2023 - Putri, Ila Fadila; Razak, Linda Arisanty; Ismawati, Ismawati (Jurnal Akuntansi, 2025)
Purpose – To determine the effect of sustainability reports and good corporate governance on financial performance. Design/Methodology/Approach – This study uses a causal associative quantitative approach, using panel data regression analysis and Eviews 12 data analysis tools. This study uses a sample of 20 companies determined based on the purposive sampling method, namely the selection of samples with certain criteria. Findings – The results of this study show that sustainability reports do not have a significant effect on financial performance. Good corporate governance with audit committee indicators does not have a significant effect on financial performance, and independent board of commissioners indicators have a significant positive effect on financial performance. Research Limitations/Implications – The limitation in this study is the lack of indicators used in measuring good corporate governance. Researchers can then develop and research other determinants that are likely to affect financial performance. Keywords: Financial Performance, Good Corporate Governance, Mining Companies, Sustainability Report